Military practice and polemic Israel's laws of warfare in Near Eastern perspective - Hasel, Michael G. (Andrews Univ. Press, 2005)
Michael Hasel examines the laws governing the siege of an enemy city as a polemic within the context of first and second millennium ancient Near Eastern military activity. He compares Israelite law with the practices of surrounding nations through the analysis of textual, iconographic, and archaeological evidence